Relasi Antara Ritual Joka Ju Dan Pola Permukiman Adat Di Desa Nggela, Kabupaten Ende-Flores - Kerong, Fabiola T. A.; Siso, Silvester M.; Toy, Melky (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2023)
The traditional settlements in Nggela Village every year carry out the Joka Ju ritual or ritual of rejecting evil which involves the entire community. This ritual is carried out to ward off all bad luck and all forms of disease and is generally carried out after getting the harvest. This research will look at the process of this traditional ritual from the preparation process to the peak ritual, and the space in the traditional settlement pattern inhabited by traditional leaders (Mosalaki) of which there are 17 people in 15 traditional houses. The research method used is a qualitative method with a naturalistic approach. In this research, the relationship between the Joka Ju ritual and traditional settlement patterns in cosmology, traditional settlement boundaries, orientation and sacred zones/cultural spaces and beliefs can be seen.